Nitrate removal using poly-o-toluidine zirconium(IV) ethylenediamine as adsorbent: Batch and fixed-bed column adsorption modelling. (February 2016) - Rahman, Nafisur; Khan, Mohammad Fazeel
Abstract: Nitrate removal from aqueous solutions was studied using poly- o -toluidine zirconium(IV) ethylenediamine (PTZE) in batch and fixed bed column experiments. The kinetic data obtained from batch experiments were analyzed by pseudo first order, pseudo second order, Elovich, intraparticle diffusion, Boyd's and Bangham's models. The adsorption data were well described by pseudo second order model. The effects of operating parameters such as flow rate (1–3 mL min −1 ), bed height (1–3 cm) and concentration (100–500 mg L −1 ) were studied in column mode. The adsorption efficiency increased with increasing initial concentration and bed height and decreased with increasing flow rate. The obtained experimental data were in good agreement with Thomas and Yoon–Nelson models, but in the case of Bohart–Adams model, low correlation coefficient was observed. Desorption of nitrate from PTZE loaded nitrate was carried out with 0.15 M NaOH and regenerated with 1 M HCl solution. The adsorbent can be used successfully upto 8 cycles of sorption–desorption processes.